Émigrés French words that turned English - Scholar, Richard (Princeton University Press, 2020)
Émigrés is a study of French words and phrases which, untranslated, have entered the English lexicon. Historians calculate that English, since 1500, has borrowed more words from French than from any other modern foreign language. While it has naturalized many of these words, some have visibly retained their foreign roots, leading varied lives in the English-speaking world while eluding translation and resisting integration. Carrying traces of their French roots in the challenges of spelling and pronunciation they pose to native users of English, often set in italic type to distinguish them from the English surrounding them, they are, so to speak, émigrés: French foreigners in our midst. It was primarily in the 1660s that a cluster of phrases and terms with French roots - à- la-mode, ennui, naïveté, caprice -came to prominence in English as Restoration England was Frenchified by Charles II and his court. More often than not these foreign words have been enthusiastically adopted by English users, as if they lent the language a certain je-ne- sais-quoi that would otherwise elude English expression and leave it tantalisingly incomplete, though occasionally the adoption of these words has met with fear and hostility, in a reflection of the ambivalent reception that has so often awaited the foreigners who count these words as part of their native language. Richard Scholar asks several interesting questions: What uses do French foreign words serve in English? To what extent have these uses changed the meanings of the words in French language and culture? And what does the study of these words reveal of the broader relations between neighbouring languages, cultures, and societies? In addressing these questions the author explores what meanings and associations these words have brought with them from the French tradition, and he places their emergence in English within the wider context of early modern social and cultural attitudes towards foreign cultures, their mediators, and the fashion for all things French"-- Provided by publisher.